2012
DOI: 10.1093/molehr/gas063
|View full text |Cite
|
Sign up to set email alerts
|

The search for biomarkers of human embryo developmental potential in IVF: a comprehensive proteomic approach

Abstract: The objective of these studies was to identify differentially expressed peptides/proteins in the culture media of embryos grown during in vitro fertilization (IVF) treatment to establish their value as biomarkers predictive of implantation potential and live birth. Micro-droplets of embryo culture media from IVF patients (conditioned) and control media maintained under identical culture conditions were collected and frozen at -80°C on Days 2-3 of in vitro development prior to analysis. The embryos were transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…With the emerging of sensitive and speciic new analytical techniques, it is possible to carry out a comprehensive analyses of the surrounding environment of pre-implantation embryos [21]. These molecular proiles are supposed to utilize with high accuracy the diferentiation of viable and non-viable embryos [22]. The identiication of new biomarkers of the embryonic secretome can result in signiicant improvements in the eiciency of IVF cycles, increasing pregnancy rate per transfer and decreasing the costs of the procedure.…”
Section: Proteomic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the emerging of sensitive and speciic new analytical techniques, it is possible to carry out a comprehensive analyses of the surrounding environment of pre-implantation embryos [21]. These molecular proiles are supposed to utilize with high accuracy the diferentiation of viable and non-viable embryos [22]. The identiication of new biomarkers of the embryonic secretome can result in signiicant improvements in the eiciency of IVF cycles, increasing pregnancy rate per transfer and decreasing the costs of the procedure.…”
Section: Proteomic Studiesmentioning
confidence: 99%
“…It was found that the level of apolipoprotein A1 correlates with blastocyst grade, but it does not correlate with implantation and pregnancy rates. Contradictory to those indings, Nyalwidhe et al [22] used MS, Western-blot, and ELISA to identify 14 diferentially regulated peptides that were then used to generate genetic algorithms being able to identify embryo transfer cycles resulting in pregnancy and cycles with failed implantation. These genetic algorithms were able to recognize with 71-84% accuracy embryo transfer cycles, which resulted in pregnancy.…”
Section: Proteomic Studiesmentioning
confidence: 99%
“…Improving assessment methods of embryonic viability will not only improve ART success rates, but will also lead to the transfer of single, rather than multiple embryos. Transferring multiple embryos in ART exposes patients to various maternal and fetal morbidities [16,48,52].…”
Section: Proteomics and Embryonic Viabilitymentioning
confidence: 99%
“…The ideal biomarker must be safe, easily, and accurately identified in a cost-effective and noninvasive or minimally-invasive manner [15]. In ART, biomarkers should have a significant potential of predicting fertilization, implantation and embryonic viability [16]. Proteomics is thus the key to improving ART success rates by identifying, quantifying, and characterizing protein profiles of the key players that determine ART success rates.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many different approaches have been suggested to reflect the embryo's function or physiological state. Several non-invasive methods assessing embryo viability and the potentiality of development have been established, such as proteomics (6), measurement of respiration rate (7), soluble human leukocyte antigen-G (8), pyruvate uptake (9) and glucose uptake (10). However, all of these methods have not been widely used in clinic because they were either expensive and required dedicated equipment, technical staff or do not provide results quickly enough to be used within the time frame of clinical IVF.…”
Section: Introductionmentioning
confidence: 99%